Facile Generation of Strained Peptidyl Thiolactones from Hydrazides and Its Application in Assembling MUC‐1 VNTR Oligomers†. Issue 9 (3rd August 2021) - Dao, Yuankun; Wang, Biao; Dong, Weidong; Zhang, Jun; Zhong, Chao; Zhang, Zhili; Dong, Suwei
Main observation and conclusion: An efficient method for the activation of C ‐terminal 4‐mecaptoproline‐ or penicillamine‐containing peptide hydrazides in ligation reactions is reported herein. The corresponding peptide hydrazides can be readily prepared using solid‐phase peptide synthesis, and subsequently activated by acetylacetone (acac) without exogenous thiol additives. Strained peptidyl thiolactones could be the possible reactive intermediates that drastically accelerate the reaction rates at the sterically demanding proline and valine sites. This developed protocol allows for sequential peptide ligations in a one‐pot manner, and expedites the assembly of mucin 1 (MUC‐1) variable number tandem repeat (VNTR) trimers in various glycosylated forms. Abstract : An efficient method for the activation of C‐terminal 4‐mecaptoproline‐ or penicillamine‐containing peptide hydrazides in ligation reactions is reported herein. The corresponding peptide hydrazides can be readily prepared using solid‐phase peptide synthesis, and subsequently activated by acetylacetone (acac) without exogenous thiol additives. Strained peptidyl thiolactones could be the possible reactive intermediates that drastically accelerate the reaction rates at the sterically demanding proline and valine sites. This developed protocol allows for sequential peptide ligations in a one‐pot manner, and expedites the assembly of mucin 1 (MUC‐1) variable number tandem repeat (VNTR) trimers in various glycosylated forms.